Thyroglossal duct cyst papillary thyroid cancer – the state of the art - Dabrowska Anna Maria (Sciendo, 2021)
Thyroglossal duct cyst is one of the most common congenital malformations in the neck area. The majority of cysts turn out to be benign tumors, however, 0.7-1.5 % of the remnants develop into carcinoma, with papillary thyroid cancer being the most frequent malignant neoplasm. The origin of the cancer has not been clearly established so far. Typically, thyroglossal duct cyst cancer is an enlarging flexible midline or slightly lateral neck mass, most often without other worrisome symptoms. The proper diagnosis can be difficult due to the rare prevalence of thyroglossal duct cyst papillary thyroid carcinoma, as well as a lack of strongly typical features distinguishing benign and malignant lesions before surgery. Thus, diagnosis is usually made postoperatively just after histopathological examination of a resected cyst. However, there are diagnostic procedures that should be considered before the surgery that may be helpful in making a proper diagnosis. These include fine-needle aspiration biopsy, computed tomography or magnetic resonance imaging. Moreover, there are some characteristics revealed through clinical and ultrasound examination that may suggest the presence of such cancer. While the Sistrunk procedure is often considered adequate, currently, there is no clear consensus about concurrent thyroidectomy or radioiodine therapy. In the article, we sum up the preoperative suggestive factors of cancer, as well as the proposed indications that can be helpful in deciding on the extent of surgery and further management.